Will high-dose heparin affect blood loss and inflammatory response in patients undergoing cardiopulmonary bypass?. (January 2021) - Braatz, Erik; Sesartic, Vanja; Liska, Jan
Introduction: We performed a randomized study to investigate if a high versus a standard dose of heparin dose during cardiopulmonary bypass could affect intra- and post-operative bleeding and reduce the inflammatory response. Methods: A total of 30 patients undergoing elective coronary artery bypass grafting were randomized into high or standard dose of heparin during cardiopulmonary bypass. Blood loss was documented peri- and post-operatively, and interleukin-6, tumor necrosis factor-α, and C3 were measured in conjunction with cardiopulmonary bypass. Results: Data from 29 patients were analyzed after exclusion of one patient. The mean initial bolus and total heparin doses were 43, 000 ± 5, 800 IU versus 35, 000 ± 4, 100 IU, (p < 0.001), and 58, 000 ± 9, 500 IU versus 45, 000 ± 7, 900 IU, (p < 0.001) in the intervention and the control group, respectively. The median intra-operative bleeding was 150 mL (interquartile range 100-325) in the control versus 225 mL (IQR 200-350) in the intervention group, p = 0.15. The median chest tube blood loss 12 hour post-operatively was 300 mL (interquartile range 250-385) in the control versus 450 mL (IQR 315-505) in the intervention group, p = 0.029. There was no significant difference between the control group and the intervention group during cardiopulmonary bypass for the measured inflammatory markers interleukin-6 (p = 0.98), tumor necrosis factor-α (p = 0.72), or C3 (p = 0.13). Conclusion: This small study showed a small increase of post-operative bleeding associated with higher heparin dosage in conjunction with cardiopulmonary bypass but did not demonstrate an effect of heparin on the inflammatory response to cardiopulmonary bypass.